Analysis of public knowledge about the risk of denture treatment by dental artisans - Failasufa, Hayyu; Arimbi, Arimbi; Kusniati, Retno (Odonto : Dental Journal, 2023)
Background: Tooth loss can be experienced by all ages, gender, ethnicity or race, which will result in reduced masticatory, speech and aesthetic functions of a person. Problems that are often found in cases of denture installation at dental technicians are patients experiencing severe infections, swelling of the face, red and swollen gums accompanied by trismus or difficulty opening the mouth. People assume that the safety of the action, hygiene, and authority possessed by dental artisans are similar to those of dentists. To find out and describe the knowledge of the people of Semarang City regarding and the risks of dentures treatment by dental artisans. Method: This typed of researched was quantitative with a descriptive observational researched design. The sampling technique was purposive sampling, used the lemeshow formula, obtained 67 respondents with the inclusion criteria of the Pedurungan district community aged 35-44 years. Result: The level of public knowledge about the risks of dentures treatment by dental artisans had good level of knowledge, namely 40 respondents (59.7%) and 26 respondents (38.8%) had sufficient knowledge Conclusion: The leveled knowledge of the people of Pedurungan district regarding the leveled of knowledge about risks of dentures treatment by dental artisans was classified as good and sufficient.